Chitosan scaffolds containing hyaluronic acid for cartilage tissue engineering - Correia, Clara R. (2011)
Scaffolds derived from natural polysaccharides are very promising in tissue engineering applications and regenerative medicine, as they resemble glycosaminoglycans in the extracellular matrix (ECM). In this study, we have prepared freeze-dried composite scaffolds of chitosan (CHT) and hyaluronic acid (HA) in different weight ratios containing either no HA (control) or 1%, 5%, or 10% of HA. We hypothesized that HA could enhance structural and biological properties of CHT scaffolds. To test this hypothesis, physicochemical and biological properties of CHT/HA scaffolds were evaluated. Scanning electron microscopy micrographs, mechanical properties, swelling tests, enzymatic degradation, and Fourier transform infrared (FTIR) chemical maps were performed. To test the ability of the CHT/HA scaffolds to support chondrocyte adhesion and proliferation, live–dead and MTT assays were performed. Results showed that CHT/HA composite scaffolds are noncytotoxic and promote cell adhesion. ECM formation was further evaluated with safranin-O and alcian blue staining methods, and glycosaminoglycan and DNA quantifications were performed. The incorporation of HA enhanced cartilage ECM production. CHT/5HA had a better pore network configuration and exhibited enhanced ECM cartilage formation. On the basis of our results, we believe that CHT/HA composite matrixes have potential use in cartilage repair.